Is routine pathological examination of hernia sac necessary? (Annals of Medical Research, 2021)
Aim: Minimally invasive hernia repair methods in which the hernia sac is not excised are applied frequently, bringing into question the necessity of routine pathological examination when the hernia sac is excised. Here, we aim to discuss the pathology results and unexpected histopathological findings of 437 sequential patients who underwent abdominal wall and inguinal hernia operation.Materials and Metods: Patients who underwent hernia surgeries and had the hernia sac sent for histopathological examinations at our hospital were retrospectively screened. Emergency and elective operated patients were included; hernia repairs without pathologic examination were excluded from the study. Pathology results were categorized into two groups as expected findings and unexpected findings.Results: A total of 437 patients were included in the study. Of these patients, 259 (59.3%) were male and the mean age was 51±16 years. Expected pathological findings were 98.9% and unexpected pathological findings were 1.1%. Unexpected pathological findings results were ranked according to frequency as follows: accessory adrenal cortex in two cases (0.4%), endometriosis in one (0.2%), skin pseudo epithelial hyperplasia in one (0.2%), and colon wall in one (0.2%).Conclusion: Histologically, unusual findings in hernia sacs were seen only in 1.1% and they were all benign. . For this reason, we think that microscopic examination of adult hernia sac specimens, other than those that cannot be clearly demonstrated to be benign macroscopically, unnecessarily increase the workload and cost.
Keywords: Hernia sac; inguinal hernia; incisional hernia; intestine; omentum